Darwinism and Human Dignity. (1st February 2007) - Dixon, Ben
James Rachels argued against the possibility of finding some moral capacity in humans that confers upon them a unique dignity. His argument contends that Darwinism challenges such attempts, because Darwinism predicts that any morally valuable capacity able to bestow a unique dignity is likely present to a degree within both humans and non-human animals alike. I make the case, however, that some of Darwin's own thoughts regarding the nature of conscience provide a springboard for criticising Rachels's claim here. Using Darwin's thoughts regarding conscience, I begin the project of grounding a revised account of human dignity in the human tendency to enshrine products of conscience within institutions. Specifically, I argue that this new account of human dignity is partly contingent upon humans creating institutions morally respectful of the values present within non-human nature.